2018
DOI: 10.1021/acssensors.8b00048
|View full text |Cite
|
Sign up to set email alerts
|

Ferromagnetic Resonance Biosensor for Homogeneous and Volumetric Detection of DNA

Abstract: The ability to detect and analyze the state of magnetic labels with high sensitivity is of crucial importance for developing magnetic biosensors. In this work, we demonstrate, for the first time, a ferromagnetic resonance (FMR) based homogeneous and volumetric biosensor for magnetic label detection. Two different isothermal amplification methods, i.e., rolling circle amplification (RCA) and loop-mediated isothermal amplification (LAMP), are adopted and combined with a standard electron paramagnetic resonance (… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
32
0

Year Published

2019
2019
2022
2022

Publication Types

Select...
7
2

Relationship

3
6

Authors

Journals

citations
Cited by 36 publications
(33 citation statements)
references
References 55 publications
1
32
0
Order By: Relevance
“…In addition, biological samples are generally not magnetic and thus do not affect the sensitivity/signal transduction in the magnetic domain, unlike how fluorescence can in the optical domain. Numerous methods have been developed for sensing the magnetically labelled target analytes in a volume [13] and on a sensor surface and some of which are used for detection of magnetically labeled RCPs including: magneto-resistive sensors [14], superconducting quantum interference devices (SQUIDs) [9,15,16,17], induction coils [18,19], optomagnetic sensors [20,21], and ferromagnetic resonance sensors [22]. The MNPs are conjugated to the RCPs by base pare hybridization forming MNP-RCP complexes which have a larger hydrodynamic size compared to the unbound MNPs.…”
Section: Introductionmentioning
confidence: 99%
“…In addition, biological samples are generally not magnetic and thus do not affect the sensitivity/signal transduction in the magnetic domain, unlike how fluorescence can in the optical domain. Numerous methods have been developed for sensing the magnetically labelled target analytes in a volume [13] and on a sensor surface and some of which are used for detection of magnetically labeled RCPs including: magneto-resistive sensors [14], superconducting quantum interference devices (SQUIDs) [9,15,16,17], induction coils [18,19], optomagnetic sensors [20,21], and ferromagnetic resonance sensors [22]. The MNPs are conjugated to the RCPs by base pare hybridization forming MNP-RCP complexes which have a larger hydrodynamic size compared to the unbound MNPs.…”
Section: Introductionmentioning
confidence: 99%
“…The colloidal stability of magnetic nanoprobes at elevated temperatures is essential for applications in assays based on the isothermal amplification of DNA (e.g., loop-mediated isothermal amplification or rolling circle amplification) [49] or PCR [50], when reaction mixtures can be heated up to +95 °C. The aggregation of nanoparticles can negatively influence assay performance.…”
Section: Resultsmentioning
confidence: 99%
“…Tian et al reported ferromagnetic resonance (FMR)-based volumetric and homogeneous biosensors for DNA detection. 148 This method quantifies the target DNA by measuring the FMR field shift of the suspension. The detection strategy for target DNA is based on an isothermal amplification followed by hybridization with detection-antibody-modified MNPs.…”
Section: Other Magnetic Bioassay Methodsmentioning
confidence: 99%
“…Tian et al reported the volumetric detection of DNA using FMR shifts. 148 Aggregation of MNPs was caused by binding of the V. cholerae target DNA sequence, which gave rise to significant FMR shifts compared to nonaggregated MNPs. However, this technique involves the insertion of MNP samples inside an electromagnetic cavity, which is not nanoscale-frequency detection.…”
Section: Other Magnetic Bioassay Methodsmentioning
confidence: 99%